(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This article describes the importance of Kazakh literature, its historical heroes, and also historical events in society and their role in modern times. Kazakh writers were interested in preserving the traditions and historical consciousness of the Kazakh people by giving them a historical signature and historical form. Readers are taught to differ good and bad by historical heroes in their works, their characteristics, description of their heroic deeds, they awaken heroism and peacefulness in the hearts of young generation through characteristics and actions of heroes. The article includes a large number of works, some of which were thematically analyzed. In particular, the article covers the historical novels of Kazakh writers, published in the 20th and 21st centuries, as well as changes and innovations in modern literature.